Oral mucosal lesions and their association with sociodemographic, behavioral, and health status factors - José Nicolau GHENO; Marco Antonio Trevizani MARTINS; Maria Cristina MUNERATO; Fernando Neves HUGO; Manoel SANT'ANA FILHO; Camila WEISSHEIMER; Vinicius Coelho CARRARD; Manoela Domingues MARTINS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The aim of this study was to evaluate the frequency of oral mucosal lesions and their associations with sociodemographic, health, and behavioral factors in a southern Brazilian population. Information was collected from participants (n = 801) using a structured questionnaire during an oral cancer screening campaign held at an agribusiness show in southern Brazil in 2009. Data were described using frequency distributions or means and standard deviations. Associations between independent variables and outcomes were assessed using the Chi-squared test. A total of 465 lesions were detected (actinic cheilitis: n = 204, 25.5%; candidiasis: n = 50, 6.2%; fibrous inflammatory hyperplasia: n = 42, 5.2%; ulceration, n = 33, 4.1%; hemangioma: n = 14, 1.7%; leukoplakia: n = 11, 1.4%). Candidiasis, actinic cheilitis, and fibrous inflammatory hyperplasia were associated significantly with literacy. Actinic cheilitis was also associated significantly with sun exposure and hat use, and leukoplakia was associated with smoking. The high frequency of oral mucosal lesions observed highlights the importance of education about risk factors. Additionally, training of health professionals, mainly those from public health services, in the use of preventive and community education strategies is needed.